Consumption of news and perception of fake news among Communication students from Brazil, Spain and Portugal - Catalina-García, Beatriz (2019)
This article contributes to the debate on the current crisis of journalism, using the results of a research by questionnaire on the perception of fake news by students of Communication Studies in Brazil, Spain, and Portugal. Research involved 300 participants in universities in these countries. Results show more similarities than differences in their ability to detect fake news and to perceive its origin and where they circulate. Among the habits of consumption of news, it is detected the abandonment of conventional media in their home supports. However, is also observed a high use of digital versions of newspapers, radios and television stations and a special preference for news that arrives via social media. Students do not have habits of reading / listening / watching all the content of a news story and focus mostly on reading the headlines and leads.